Recent developments in the research and control of Theileria annulata. Proceedings of a workshop - Dolan, T.T. (International Laboratory for Research on Animal Diseases, 1992)
This workshop was carried out to review the present distribution and economic importance of tropical theileriosis; the current state of control measures for this disease including use of acaricides, immunization and chemotherapy, the state of development of improved epidemiological preventive and diagnostic tools; and how ILRAD (International Laboratory for Research on Animal Diseases) might contribute either directly to research in these areas or indirectly by provision of reagents or transfer of technologies. The first part presents country reports including China, India, Iran, Morocco, Sudan, Turkey and USSR. The rest of the paper discusses modeling, current methods of diagnosis and control, immunology, and biology with particular reference to Theileria annulata.